Interferon add-on therapy increased clinical cure significantly for interferon-experienced chronic hepatitis B patients with low HBsAg - Yang, Xiaoan; Zhang, Ka; Xu, Qihuan; Shu, Xin; Mo, Zhishuo; Xie, Dongying; Gao, Zhiliang; Deng, Hong (Frontiers in Immunology, 2022)
Currently, interferon add-on therapy brings hope for clinical cure of chronic hepatitis B patients with low HBsAg. However, in clinical practice patients with poor responses to their first interferon therapy were often switched to nucleos(t)ide analog therapy and then labeled as unsuitable patients for interferon therapy. Even if their HBsAg levels dropped to a low level, they were reluctant or not recommended to take interferon again, which caused them to miss out on interferon add-on therapy and clinical cure. Therefore, it is urgent to elucidate the effectiveness of interferon add-on therapy to get clinical cure for these interferon-experienced patients with low HBsAg. The purpose of this study was to investigate whether interferon-experienced patients could achieve the same HBsAg clearance and HBsAg seroconversion rates as interferon-naive patients. Also, the associated factor of HBsAg clearance and seroconversion were aimed to be clarified. 292 patients, including 85 interferon-experienced patients, were enrolled with HBsAg < 1500 IU/ml, HBeAg negative and HBV-DNA negative. And then, peg-interferon α-2b add-on therapy was performed. The results showed that he week 48 HBsAg clearance and seroconversion rates of all patients were 29.8% and 22.0%. There was no statistically significant difference between interferon-experienced and interferon-naive patients in week 48 HBsAg clearance and seroconversion rates, suggesting satisfactory clinical cure of the interferon add-on therapy for interferon-experienced patients. The age, baseline HBsAg, and week 12 HBsAg were negative correlated factors for week 48 HBsAg clearance and seroconversion. Furthermore, the age, baseline HBsAg and week 12 HBsAg for predicting the week 48 HBsAg clearance were cut off at 40.5 years, at 52.0 IU/ml and at 34.99 IU/ml, and for predicting seroconversion were cut off at 40.5 years, at 181.9 IU/ml and at 34.99 IU/ml, correspondingly. Significantly, interferon-experienced patients with low HBsAg were suggested with interferon add-on therapy to achieve clinical cure as soon as possible. This research provided evidences and cut-offs for the interferon add-on therapy against chronic hepatitis B.